Cell-mediated immunity to HIV-1 in Walter Reed stages 1-6 individuals: correlation with virus burden. - Trauger, R J (1993)
Cell-mediated immunity (CMI) to human immunodeficiency virus-1 (HIV-1) was assessed in a blinded fashion for a patient group (n = 79) representing Walter Reed (WR) stages 1-6. At the same time, viral load was quantitatively measured by two different methods, specifically, virus isolation and HIV viral DNA copy number as measured by the polymerase chain reaction (PCR). After unblinding it was determined that the ability to generate a lymphoproliferative response to an inactivated gp120-depleted HIV (HIV-ag) and tetanus toxoid diminished with advancing WR staging, with complete anergy to HIV-ag and tetanus at stage 6. As a group, individuals whose peripheral blood mononuclear cells (PBMC) proliferated to HIV-ag were either virus isolation negative or produced low levels of virus as measured by p24 antigen (< 250 pg p24) on day 7. Similarly, HIV DNA copy number in the HIV-ag responders was low (< 200 copies/4 x 10(5) PBMC). In contrast, antigen proliferation to tetanus toxoid did not correlate with virus load. Thus, clinical progression as defined by the WR staging system appears to coincide with a loss of CMI to HIV. More importantly, the low viral load measured in HIV-ag responders suggests a link between viral burden and CMI to HIV which might be exploited in the design of immunotherapies for HIV-infected individuals.